The Relationship of Physical Activity with Restless Legs Syndrome in Chronic Kidney Disease Patients in the Hemodialysis Room of Subang District Hospital - Syifa Lestari; Rosiah Rosiah; Minanton Minanton (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Restless legs syndrome (RLS) is a sensorimotor disorder that affects a person's desire to move the legs. Physical activity is considered to be one way to reduce RLS symptoms. The purpose of this study was to analyze the relationship of physical activity with RLS in patients with chronic kidney disease (CKD) in the hemodialysis room of RSUD Kab Subang. This research is a type of quantitative research, correlational descriptive research design using cross-sectional. The sample in this study was 62 respondents, with purposive sampling techniques. Data collection using the Global Physical Activity Questionaire (GPAQ) and International Restless Legs Syndrome Group (IRLS) questionnaires, and data analysis using the spearmen rank test. The results showed that most respondents had a low level of physical activity, with a prevalence of 64.5%, and most respondents experienced severe symptoms of RLS, with a prevalence of 40.3%. Statistical tests show that there is a relationship between the physical activity variable and RLS (p-value 0.001), with the coefficient value is -0.741. It can be concluded that there is a solid relationship between physical activity and RLS in CKD patients in the hemodialysis room of RSUD Kab Subang with an antagonistic relationship direction. It is expected that nurses can intervene in chronic kidney disease patients to perform physical activity in accordance with their ability to reduce RLS.